2015
DOI: 10.5194/acp-15-6851-2015
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous reaction of peroxyacetic acid and hydrogen peroxide on ambient aerosol particles under dry and humid conditions: kinetics, mechanism and implications

Abstract: Abstract.Hydrogen peroxide (H 2 O 2 ) and organic peroxides play important roles in the cycle of oxidants and the formation of secondary aerosols in the atmosphere. Recent field observations have suggested that the budget of peroxyacetic acid (PAA, CH 3 C(O)OOH) is potentially related to the aerosol phase processes, especially to secondary aerosol formation. Here, we present the first laboratory measurements of the uptake coefficient of gaseous PAA and H 2 O 2 onto ambient fine particulate matter (PM 2.5 ) as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 86 publications
(107 reference statements)
2
32
1
Order By: Relevance
“…Using the box model, the daily-averaged lifetime of atmospheric H 2 O 2 , MHP and PAA during the whole of Phase I and Phase III were calculated to be about 2.1, 2.3 and 3.0 h, respectively. This is comparable to the literature results with the inclusion of heterogeneous reaction (Liang et al, 2013b;Wu et al, 2015), but notably shorter than the recent studies conducted by Khan et al (2015) and Nguyen et al (2015) without the coupling of the heterogeneous process. Although dry deposition is thought to dominate the atmospheric lifetime of peroxides in previous studies (Reeves and Penkett, 2003), its role in the lifetime of atmospheric peroxides is insignificant during Wangdu Campaign 2014.…”
Section: Heterogeneous Uptake Of Peroxides By Aerosolsupporting
confidence: 80%
See 3 more Smart Citations
“…Using the box model, the daily-averaged lifetime of atmospheric H 2 O 2 , MHP and PAA during the whole of Phase I and Phase III were calculated to be about 2.1, 2.3 and 3.0 h, respectively. This is comparable to the literature results with the inclusion of heterogeneous reaction (Liang et al, 2013b;Wu et al, 2015), but notably shorter than the recent studies conducted by Khan et al (2015) and Nguyen et al (2015) without the coupling of the heterogeneous process. Although dry deposition is thought to dominate the atmospheric lifetime of peroxides in previous studies (Reeves and Penkett, 2003), its role in the lifetime of atmospheric peroxides is insignificant during Wangdu Campaign 2014.…”
Section: Heterogeneous Uptake Of Peroxides By Aerosolsupporting
confidence: 80%
“…During these case study phases, 75 % of the wind speed data were ≤ 2.2 m s −1 and the mean value was 1.6 m s −1 . It has been shown that the atmospheric lifetimes of peroxides are on the order of several hours as reported previously Wu et al, 2015), implying that the effect of regional transport or dilution on the concentrations of atmospheric peroxides was of little significance over Wangdu. Hence, the regionalscale transport can be excluded in our box model and the budgets of peroxides are, to a large extent, dependent on local chemical processes during the observation.…”
Section: Peroxide Simulationmentioning
confidence: 67%
See 2 more Smart Citations
“…The first-order rate constants representing dry deposition are d PAN and d PAA . Experimental work (Wu et al, 2015) on the uptake of PAA to ambient aerosol indicates an uptake coefficient (γ ) of ≈ 3 × 10 −4 . Using the simplified expression (1) for the heterogeneous loss-rate constant (k het ) of a trace gas to an aerosol particle:…”
Section: Production and Loss Of Pan And Ch 3 C(o)oohmentioning
confidence: 99%